Origem e distribuição dos nervos femorais em fetos suínos (SUS Scrofa Domesticus – Linneaus, 1758) do cruzamento das linhagens Dan Bred e AGPIC337 - Herrera, Gustavo Cavinato (2016)
He studied in 30 pig fetuses from the crossing of lines Dan Bred and AGPIC337, stillbirths, the origin and distribution of the femoral nerve, which were fixed in 10% formaldehyde solution. In 96.67% of the animals the number of lumbar vertebrae were six and seven 3,33%. The femoral nerve originated from L4 and L5 (66,67%), L5 and L6 (26,67%) and L3 and L4 (6,66%). Regarding its distribution branches issued for the psoas major, psoas minor, iliacus, pectineus, vastus, through vast, vastus lateralis and rectus femoris in 100% of cases, 43.33% for the Sartorius and 6.66% for gracile.